2010
DOI: 10.3109/13682820903470569
|View full text |Cite
|
Sign up to set email alerts
|

Assessing disordered speech and voice in Parkinson's disease: a telerehabilitation application

Abstract: Background: Patients with Parkinson's disease face numerous access barriers to speech pathology services for appropriate assessment and treatment. Telerehabilitation is a possible solution to this problem, whereby rehabilitation services may be delivered to the patient at a distance, via telecommunication and information technologies. A number of studies have demonstrated the capacity of telerehabilitation to provide reliable and valid assessments of speech, voice and language. However, no studies have specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
95
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 35 publications
7
95
0
8
Order By: Relevance
“…Pre and post treatment, the majority saw telepractice as a way to improve access to healthcare, save time and money and believed telepractice to be a viable option to FTF therapy. These findings are consistent with much of the literature, 19,30,40,41 with patients' perception of telepractice services in general to be very positive. The results also align with the comments made by Mashima et al 25 about the benefits of delivering voice therapy via telepractice.…”
Section: Discussionsupporting
confidence: 90%
“…Pre and post treatment, the majority saw telepractice as a way to improve access to healthcare, save time and money and believed telepractice to be a viable option to FTF therapy. These findings are consistent with much of the literature, 19,30,40,41 with patients' perception of telepractice services in general to be very positive. The results also align with the comments made by Mashima et al 25 about the benefits of delivering voice therapy via telepractice.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, caregivers were satisfied with telepractice screening and assessment (33,38,41), and in one study parents even showed a preference for telepractice services (38). These results are consistent with research into adult speech pathology clients, which has also reported high satisfaction with telepractice assessment (204)(205)(206)(207)(208). However, telepractice may not be satisfactory for all caregivers.…”
Section: Discussionsupporting
confidence: 87%
“…If the method-comparison study concludes that the techniques are equivalent, the new method can be introduced into clinical care (241). This study design has previously been used in a number of studies into the use of telepractice for speech and language assessment or screening for paediatric clients (33)(34)(35)(36)(37)(38)(39)(40)(41) and adult clients (199,204,205,207,(242)(243)(244)(245). In my study, the new technique evaluated was speech and language screening via telepractice.…”
Section: Methodsmentioning
confidence: 99%
“…Significant improvement in vocal intensity post therapy was reported, and the results were in good agreement with those obtained by Ramig et al (2001) for in-person therapy. Constantinescu et al (2010aConstantinescu et al ( , 2010bConstantinescu et al ( , 2011 reported a series of studies demonstrating the utility of telepractice in voice assessment and treatment of individuals with Parkinson's disease. In their first study (Constantinescu et al, 2010a), the authors examined the validity of assessing speech and voice in 61 individuals with Parkinson's disease in telepractice versus in-person sessions and reported comparable results for vocal sound pressure level, phonation time, pitch range, sentence intelligibility, and communication efficiency in reading.…”
Section: Telepractice and Voice Treatmentmentioning
confidence: 99%
“…Constantinescu et al (2010aConstantinescu et al ( , 2010bConstantinescu et al ( , 2011 reported a series of studies demonstrating the utility of telepractice in voice assessment and treatment of individuals with Parkinson's disease. In their first study (Constantinescu et al, 2010a), the authors examined the validity of assessing speech and voice in 61 individuals with Parkinson's disease in telepractice versus in-person sessions and reported comparable results for vocal sound pressure level, phonation time, pitch range, sentence intelligibility, and communication efficiency in reading. Furthermore, the authors reported a case report (Constantinescu et al, 2010b) validating the utility of online delivery of LSVT.…”
Section: Telepractice and Voice Treatmentmentioning
confidence: 99%